REDUCTION IN THE REGENERATION ENERGY OF CO2 CAPTURE PROCESS BY IMPREGNATING AMINE SOLVENT ONTO PRECIPITATED SILICA - Quang, Dang Viet; Rabindran, Aravind V.; El Hadri, Nabil; Abu-Zahra, Mohammad R. M. (European Scientific Journal, ESJ, 2013)
High energy required for the regeneration of aqueous amine solution is a great challenge for conventional CO2 capture technology to be deployed on large scale. Finding novel adsorbent with low regeneration energy and cost-effectiveness for CO2 capture is an impetus for researchers. In this study, precipitated silica (PS) was synthesized and impregnated with various amines including 2-aminomethylpropanol (AMP), monoethanolamine (MEA), diethanolamine (DEA) and polyethyleneimine (PEI) to produce solid adsorbents. The CO2 adsorption capacity, heat capacity, and adsorption heat of adsorbents were determined. The results were used to calculate the regeneration heat of CO2 adsorption process, which then was compared with the conventional aqueous MEA 30 wt% based process. The results indicated that MEA impregnated PS (60 wt%) has the highest CO2 adsorption capacity; up to 5.3 mmole/g and PEI impregnated PS (50 wt%) has the lowest adsorption capacity among prepared solid adsorbents; 2.9 mmole/g, which is, however, higher than that of aqueous MEA 30 wt% (2.7 mmole/g). The regeneration heat required for the solid adsorbents substantially decreased in comparison with aqueous MEA 30 wt%. Regeneration heat required for PEI impregnated PS (50 wt%) was 2080 kJ/kg of CO2 that is 46.7% lower than that of aqueous MEA 30 wt%. The obtained results demonstrated that the impregnation of amine onto PS is a viable method to reduce the regeneration energy of CO2 capture process.